2017
DOI: 10.1051/epjconf/201715304019
|View full text |Cite
|
Sign up to set email alerts
|

Geant4-DNA simulation of DNA damage caused by direct and indirect radiation effects and comparison with biological data.

Abstract: Abstract. In this work we present results obtained in the frame of the BioQuaRT project. The objective of the study was the correlation between the number of radiation-induced double strand breaks (DSB) of the DNA molecule and the probability of detecting nuclear foci after targeted microbeam irradiation of cells with protons and alpha particles of different LET. The former were obtained by simulation with new methods integrated into Geant4-DNA that permit calculating the number of DSB in a DNA target model in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…It should be noted that the scoring method for DNA damage can strongly influence the final yield of simulated DSB induction. As mentioned in our previous works [35,46,47], a change in the parameters to score direct and/or indirect strand breaks can greatly increase the yield of DSB. Moreover, a chemical simulation end-time of 10 ns has been suggested in our computation chain instead of the 2.5 ns currently used when considering the cell nucleus model filled with heterochromatin and euchromatin [46].…”
Section: Discussionmentioning
confidence: 90%
“…It should be noted that the scoring method for DNA damage can strongly influence the final yield of simulated DSB induction. As mentioned in our previous works [35,46,47], a change in the parameters to score direct and/or indirect strand breaks can greatly increase the yield of DSB. Moreover, a chemical simulation end-time of 10 ns has been suggested in our computation chain instead of the 2.5 ns currently used when considering the cell nucleus model filled with heterochromatin and euchromatin [46].…”
Section: Discussionmentioning
confidence: 90%
“…Instead, the assumptions that have been made, 10 bp damage separation and damage determined by an energy range probability, can only be described as conditions that produce reasonable results when compared to experiment. For example, recent work from Villagrasa et al 70 showed that using an energy threshold as the mechanism for direct strand break reproduces the experimental yield of 53BP1 foci. The impact of such parameters used for predicting DNA damage for electrons was recently presented by Lampe et al 71 Since the mechanism may not have been identi-ed, applying these conditions to a larger, more complex, system requires caution.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, it should also be noted that the yield of DNA DSBs can vary depending on the method used to score DNA damage. To illustrate this point, it was shown in previous study that the criterion used to determine direct damage can strongly influence the final DSB yields, even if the proportion of direct damage is lower than the proportion of indirect damage. In our simulation chain, the best fit to the experimental data was obtained using a threshold value of 17.5 eV instead of a linear probability from 5 to 37.5 eV .…”
Section: Discussionmentioning
confidence: 99%